(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present study aims to analyse and establish association between occupational stress, job satisfaction and job leaving intention among employees due to merger in the Indian banking sector. Four cases of merger involving ten public sector banks were studied. Various statistical tools have been used to assess the sample data consisting of 291 employees collected from field survey. Empirical findings indicates significant difference in job stress, level of satisfaction and job leaving intention across demographic variables. With the increase in the level of stress due to merger, the job satisfaction of employees reduces, whereas positive relationship between the stress and the job leaving intention due to merger was found. The findings of the present study will be helpful for the top management to understand the behaviour of employees during mergers & acquisitions and formulate such policies to help them cope with the negative influence of merger.